Citizenship Policies in the New Europe - Bauböck, Rainer; Perchinig, Bernhard; Sievers, Wiebke (IMISCOE Research, 2007)
In May 2004 ten new Member States joined the European Union. This enlargement has greatly increased the diversity of historic experiences and contemporary conceptions of statehood, nation-building and citizenship within the Union. In contrast with the old Member States, many of the new ones have not existed as independent states within their present borders for more than two generations. Citizenship Policies in the New Europe describes the citizenship laws in each of the ten new countries and analyses their historical background. Turkey has been added as the largest source country of immigration into the fifteen old Member States because it illustrates the increasing interaction between citizenship laws in migrant sending and receiving countries. Citizenship Policies in the New Europe complements two volumes on Acquisition and Loss of Nationality published earlier in the same series and that present comparative analyses of citizenship regulations in the fifteen old Member States. Citizenship Policies in the New Europe is part of the IMISCOE Research series. Two other publications on the same subject, "http://www.aup.nl/do.php?a=show_visitor_book&isbn=9789053569498">Acquisition and Loss of Nationality, were released earlier this year. Authors: Andrea Bar ová, Eugene Buttigieg, Agata Górny, Priit Järve, Zeynep Kadirbeyoglu, Mária Kovács, Kristine Kruma, Andre Liebich, Dagmar Kusá, Felicita Medved, Judit Tóth, Nikos Trimikliniotis This title is available in the OAPEN Library - http://www.oapen.org.